Differences on Geochemical Characteristics and Their Implicating Significances of Nitrogen in Coal-Derived Gas and Oil-typed Gas in China - Xiaobo, Wang; Jian, Li; Chunxia, Yang; Zhisheng, Li; Jianfa, Chen; Yue, Zheng; Yifeng, Wang; Jin, Li; Chunlong, Yang; Aisheng, Hao; Shouguo, Ge (Frontiers in Earth Science, 2021)
Natural gases in China are mainly coal-derived gas, with assistance from oil-typed gas. At present, many genetic identification methods, from hydrocarbon composition and isotope to light hydrocarbon and biomarker indexes, have been formed, but combined methods from non-hydrocarbon gases are lacking. Based on compositions and isotopes geochemical characteristics and the differences of non-hydrocarbon nitrogen gas in coal-derived gas and oil-typed gas, and combining the isotopic geochemical characteristics of non-hydrocarbon helium, the comprehensive identification methods of coal-derived gas and oil-typed gas for hydrocarbon gases according to the associated non-hydrocarbon gases of nitrogen and helium are established and the preliminary applications have been engaged. The main recognitions are as follows:1)Coal-derived gas generally has relatively lower nitrogen abundance, mainly distributed from 0 to 31.2% with main frequency from 0 to 2%. Oil-typed gas, on the other hand, usually has relatively higher nitrogen abundance, mainly distributed from 1.1 to 57.1% with main frequency from 2 to 16%. 2) Coal-derived gas generally has relatively heavier nitrogen isotope values, mainly distributed from -8 to 19.3‰ with main frequency from -8 to 8‰.Oil-typed gas usually has relatively lower nitrogen isotope values, mainly distributed from -10.6 to 4.6‰ with main frequency from -8 to 4‰.3)The geochemical characteristic differences of coal-derived gas and oil-typed gas are mainly due to the fact that the sapropel parent material is relatively rich in nitrogen element and rich in light δ14N, while the humic parent material is relatively poor in nitrogen element and rich in heavy δ15N. The differences on thermal maturity of source rocks, the redox conditions of source rock sedimentary environment, and the salinity of water body are also important effective factors.4)Differences on nitrogen abundances and isotopes in coal-derived gas and oil-typed gas have great significance in genetic identification. The genetic identification chart of R/Ra-δ15N for organic and inorganic nitrogen in natural gas and the comprehensive joint identification charts of R/Ra-δ15N-N2 of nitrogen and helium for coal-derived gas and oil-typed gas have been established, and are of great reference in investigating the origins and sources of natural gas and guiding natural gas exploration in China.